2021
DOI: 10.1007/s11130-021-00898-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Physicochemical Characterization of Walnut Flour, a By-product of Oil Extraction

Abstract: The by-product of walnut oil (Juglans regia L.) extraction is a press cake rich in polyunsaturated fatty acids and other bioactive compounds. From this cake, walnut flour is obtained by a milling process. The composition and a physicochemical characterization of walnut flour was performed: proximal composition, mineral content, and fatty acid and amino acid profiles were measured. Besides, antioxidant capacity and water and oil holding capacities were determined. Walnut flour has 55% of lipids with an optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Phenolic compounds, hydrolyzable tannins, and flavanols are the major components in walnut flour [45]. Similar to our results, Burbano and Correa [46] reported that the total phenolic content of walnut flour is 10.9 ± 0.3 mg GAE/g. Santos et al [47] studied the effect of roasting conditions on the composition and antioxidant properties of defatted walnut flour and they observed that walnut flour contains 20 mg GAE/g.…”
Section: Amount Of Phenolic Compounds and Flavonoid Compoundssupporting
confidence: 90%
“…Phenolic compounds, hydrolyzable tannins, and flavanols are the major components in walnut flour [45]. Similar to our results, Burbano and Correa [46] reported that the total phenolic content of walnut flour is 10.9 ± 0.3 mg GAE/g. Santos et al [47] studied the effect of roasting conditions on the composition and antioxidant properties of defatted walnut flour and they observed that walnut flour contains 20 mg GAE/g.…”
Section: Amount Of Phenolic Compounds and Flavonoid Compoundssupporting
confidence: 90%
“…The water and oil absorption of potato starch and kañiwa and tarwi flours were determined as described in a previous work. 17 Samples (W 0 = 1 g) were added with 30 mL of water, vigorously shaken and left to rest at room temperature (30 min). Samples were centrifuged (Thermo Scientific SL 40R, Langenselbold, Germany) at 2000×g (10 min at 20 °C).…”
Section: Water and Oil Absorptionmentioning
confidence: 99%
“…Similarly, the lack of gluten-forming proteins is an issue in the development of baked goods or pasta. Thus, a deeper knowledge about the techno-functionality of nut flours is fundamental to improving their use, and especially to valorize nut press cakes, which are the remnant after the extraction of oil from the nuts, deriving from the oil industry [ 62 , 63 ].…”
Section: Classification Nutritional and Technological Functionality O...mentioning
confidence: 99%